(untitled) (Strathmore Law Review, 2025)
As the race for Synthetic Biology research and governance heats up between global superpowers like the United States and China, developing countries risk being left behind. To prevent this from happening, it is crucial that such countries, like Kenya, embrace this cutting-edge biotechnology to promote their socio-economic growth. The interest in this area is important, especially for these countries, owing to the immense benefits the novel biotechnology promises. However, the pursuit of Synthetic Biology development must be undertaken with caution, as it poses catastrophic risks, such as engineered or accidental pandemics from pathogen release. This study explores the potential benefits of Synthetic Biology in Kenya, evaluates the risks requiring regulation, and proposes a structure of a potential legal solution that balances the pursuit of bio-innovation with the need to prevent pathogen risks. Through a rigorous analysis, this research seeks to demonstrate that developing countries can effectively manage the risks associated with Synthetic Biology development and protect their citizens by adopting a robust legal and institutional framework. This study’s findings have global implications, as they provide a blueprint for other similarly situated developing countries. The propositions in this paper are a call to action for policymakers to prioritise responsible governance of Synthetic Biology and mitigate the potential catastrophic risks of this revolutionary biotechnology. Being a double-edged sword, this study offers a roadmap to ensure that Synthetic Biology is navigated safely and responsibly.